Spatio-temporal analysis of the droughts in Cali, Colombia and their primary relationships with the El Nino-Southern Oscillation (ENSO) between 1971 and 2011 - Cerón, Wilmar Loaiza (2020)
This paper analyzed the spatio-temporal variability of droughts in Cali, Colombia and their primary relations to the El Nino Southern Oscillation (ENSO). The Standardized Precipitation Index (SPI) was used to detect drought events from monthly rainfall data of 24 stations well spread over Cali during 1971-2011. The SPI provided the drought intensity, magnitude, frequency, and the minimum rainfall thresholds, mainly on an annual scale (SPI-12). Eighty percent of the stations reported four events with dry conditions in Cali: 1976-1977, 1983-1984, 1990-1992 and 2009-2010. The ENSO influence was evaluated using the correlation and wavelet transform analyses. Significant (non-significant) negative correlations between SPI-12 in the northern (southern) part of Cali, the multivariate ENSO Index (MEI), and Sea Surface Temperature (SST) Nino 3.4 and Nino 4 indices were observed. The wavelet coherence analysis showed significant coherencies between ENSO and SPI-12: at interannual scale (4-6 years), the phase difference of-135o generates a lag of 6-9 months between the minimum peak of the SPI-12 and the maximum peak of the indices. On the quasi-biennial scale (2-3 years), the phase difference of-180o suggests that the maximum wet (dry) conditions coincide with the mature stage of the La Nina (El Nino) event; and on the decadal scale (8-16 years), the decreases (increases) in rainfall precede the El Nino (La Nina) mature stage by approximately 10-18 months. These results are relevant for seasonal forecasting, since changes in SST in the equatorial Pacific may take place 6-18 months ahead of the dry conditions in Cali. © 2020 Universidad Nacional Autonoma de Mexico.